Synthesis of Fe(III)-IIPs (Ion Imprinted Polymers): Comparing Different Concentrations of HCl and HNO3 Solutions in the Fe(III) Polymer Extraction Process for Obtaining the Largest Cavities in Fe(III)-IIPs - Novianty; Jaya Edianta; Jorena; Khairul Saleh; Akhmad Aminuddin Bama; Erry Koriyanti; Menik Ariani; Idha Royani (Science and Technology Indonesia, 2023)
This study was conducted to synthesize Fe (III)-IIPs by free radical polymerization using the cooling-heating method. Cooling processat -5◦C for 1 hour, as well as heating at 75◦C, 80◦C, and 85◦C maintained for 3 hours, 2 hours and 1 hour, respectively. The Fe (III)-IIPs synthesis process involved Fe(NO3)3 with an average diameter of 18.23 nm, methacrylic acid (MAA), ethylene glycol dimethacrylate (EGDMA), benzoyl peroxide (BPO) and ethanol, each of which plays a role as an analyte, functional monomer, cross-linker, initiator, and porogen. The result of the polymerization process was a polymer containing ions namely Fe(III) polymer. The ions need to be removed by the extraction process to produce Fe(III)-IIPs, which act as absorbents. Furthermore, the extraction process is very influential in the process of losing ions and the formation of cavities or templates in the polymer body. The number of cavities formed tends to affect the ability of Fe(III)-IIPs to identify the target ion which has similar physical and chemical properties to the shape of the Fe(III)-IIPs cavity. The extraction process was carried out on Fe(III) polymer samples using HCl and HNO3 solutions with varying concentrations of 3 M and 6 M, respectively. The transmission percentage of FTIR analysis showed that for samples of Fe(III)-IIPs HCl 3 M and 6 M were 94.258% and 95.666%, while for Fe(III)-IIPs HNO3 3 M and 6 M were 92.735%, respectively. The largest percentage was shown in the 6 M HCl IIPs sample, which indicated that there were several ions lost from the polymer body after the extraction process. This is also reinforced by the results of the SEM analysis processed with Matlab, which showed 498 cavities with a distribution of voids on a scale of <100 nm, totaling 470.